Impact of an occupational gym program on flexibility in office workers - Matos, M. (2015)
The problem of work-related musculoskeletal disorders is a rising concern in the companies. Thus, occupational gym has emerged as a possible solution to this problem because it leads to changes in the lifestyle by promoting health and physical activity. In this regard, this study purposes to evaluate the impact of an occupational gym program in the neck and shoulder flexibility in office workers. In order to evaluate the levels of flexibility, a universal goniometer was used for pre and post occupational gym program implementation. The program had an extension of three months, with 15 minutes sessions twice a week. The sample consisted in an intervention group comprised of 30 elements and a control group composed of 8 elements. The results suggest that there were improvements in flexibility at the cervical spine and shoulder segments levels. The increase on flexibility between the two time points in the intervention group was significant, unlike the control group that presented only slight improvements.